Article Review Gingivitis, Etiology and Prevention (Texas Journal of Medical Science, 2022)
Since the maintenance of the structures that support the practice of dentistry is affected by gingivitis, in this article was reviewed the etiology points for gingivitis and prevention methods to avoid gingivitis disease.